On the Legal Relationship Between a Father and his Natural Child - Flaišman, Yôsēf (Zeitschrift für altorientalische und biblische Rechtsgeschichte, 2000)
This study discusses how a natural child obtained the status of heir according to some Ancient Near Eastern legal sources. We are of the opinion that from an analysis of the earliest relevant legal sources (Lipit Ishtar 27 and Codex Hammurabi 170- 171 and 144- 145) the following can be concluded: a natural child was considered legitimate issue as long as there were legal links between his parents which the lawgiver deemed sufficient to grant the child the legal status of son and heir.